Bourgeoisie : état d'une classe dominante - de Brunhoff, Suzanne; Garo, Isabelle; Serfati, Claude; Wagner, Anne-Catherine; Zalia, Pierre-Paul (Paris : Syllepse, 2001)
Bibliotheek François Vercammen
Frans
Monografie